The swiss family Robinson - Wyss David Johann 1743-1818; Johann David Wyss (Pensacola Christian Collage : Johann David Wyss, 2000)
Relates the fortunes of a shipwrecked family as they adapt to life on an island with abundant animal and plant life.
Q
860